What makes voters turn out: The effects of polls and beliefs - Marina Agranov; Jacob K. Goeree; Julian Romero; Leeat Yariv (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2016)
We use laboratory experiments to test for one of the foundations of the rational voter paradigm - that voters respond to probabilities of being pivotal. We exploit a setup that entails stark theoretical effects of information concerning the preference distribution (as revealed through polls) on costly participation decisions. We find that voting propensity increases systematically with subjects' predictions of their preferred alternative's advantage. Consequently, pre-election polls do not exhibit the detrimental welfare effects that extant theoretical work predicts. They lead to more participation by the expected majority and generate more landslide elections.
Keywords: C92; D02; D72; 330; Collective Choice; Polls; Strategic Voting